Handbook of stress, trauma, and the family - Catherall, Donald Roy, 1946- (Brunner-Routledge psychosocial stress series., 2004)
This well-written and long-overdue handbook will provide students, clinicians and teachers with the most up-to-date and thorough study of the subject available, and it is destined to become a classic.